Cognitive Mechanisms of Communicative Behaviour of Representatives of Various Linguistic Cultures of the East - Asadchykh, Oksana V.; Mazepova, Olena V.; Moskalenko, Alla M.; Poinar, Liubov M.; Pereloma, Tetiana S. (International Journal of Criminology and Sociology, 2021)
Communicative behaviour is primarily based on the understanding of the ways a person interacts with other members of society and how much this reflects the cultural component of the communication process. This also includes the structure of discourse, which affects the communicative content of communication. The relevance of studying the specifics of organising discourse by representatives of oriental linguistic cultures is conditioned by the need to understand the deep cognitive mechanisms of their communicative behaviour in the context of the ever-increasing globalisation of the modern world. The novelty of the study is that it analyses some key factors that have a direct impact on the formation of communicative behaviour of carriers of the eastern mentality. The paper presents some deep aspects of the formation of a communicative culture in the traditions of the East, the study of which is of particular interest in the context of the growing need for successful intercultural communication. Communicative behaviour is analysed in the context of the correlation of language and culture, language and national mentality, language and consciousness. The practical significance of the study is determined by the need to form a global communicative space and structure the worldview aspect of intercultural interaction.